Short interfering RNAs targeting a vampire-bat related rabies virus phosphoprotein mRNA - Ono,Ekaterina Alexandrovna Durymanova (2017)
Abstract The aim of this study was to assess the in vitro and in vivo effects of short-interfering RNAs (siRNAs) against rabies virus phosphoprotein (P) mRNA in a post-infection treatment for rabies as an extension of a previous report (Braz J Microbiol. 2013 Nov 15;44(3):879-82). To this end, rabies virus strain RABV-4005 (related to the Desmodus rotundus vampire bat) were used to inoculate BHK-21 cells and mice, and the transfection with each of the siRNAs was made with Lipofectamine-2000™. In vitro results showed that siRNA 360 was able to inhibit the replication of strain RABV-4005 with a 1 log decrease in virus titter and 5.16-fold reduction in P mRNA, 24 h post-inoculation when compared to non-treated cells. In vivo, siRNA 360 was able to induce partial protection, but with no significant difference when compared to non-treated mice. These results indicate that, despite the need for improvement for in vivo applications, P mRNA might be a target for an RNAi-based treatment for rabies.